Isotopic niche alteration of a predator fish in a dammed Amazonian black water river - Aguiar-Santos, Jamerson; deHart, Pieter A. P.; Forsberg, Bruce Rider; Freitas, Carlos E. C. (Journal of Fish Biology, 2022)
Although many upstream effects of a dam on the trophic ecology of fish have been reported, little is known about their downstream effects on the isotopic niche of Amazonian predator fish. The authors used stable isotope analysis of δ13C and δ15N to determine the downstream effects of damming of the Uatumã River on the niche width, carbon energy sources and trophic position of peacock bass Cichla temensis comparing with a free-flowing river in the Amazon basin, Brazil, during the peak flood and early falling water period of 2020. They found that the C. temensis population of the undammed river had a smaller niche width than the C. temensis population of the dammed river, despite the greater number of prey trophic levels utilized and the higher trophic position of C. temensis individuals. The results demonstrate that in both rivers there is a gradual shift in the contribution of prey fish sources to the diet of C. temensis throughout its growth, even among adult individuals. They conclude that the isotopic niche of C. temensis was altered by damming during the period of late high water to early low water in the Uatumã River. © 2022 Fisheries Society of the British Isles.
Keywords: Amazon basin; Carbon energy sources; Uatumã River; Trophic niche; Rio Uatumã